ASPEK HUKUM PADA PROFESI AKUNTAN PUBLIK - Wisnu Wijayanto (Akademi Akuntansi YKPN Yogyakarta, 2008)
The public accountant has become an important part in assuring the financial information transparency either for the shareholders or for other users. Professionals in the field of accountancy have legal responsibility related to the services offered to the society. The determination on how far the auditor has to be responsible for the correctness of financial report has been a relevant thing to the accountant profession and to society. Various possibilities of legal prosecution faced by the auditors are described in this article dealing with the assurance services offered. The legal prosecution is related to both private law and criminal law which have legal effects respectively. From the auditor point of view, the auditor is not necessary to have full legal responsibility on the mistakes in the financial report. The auditor cannot act as the guarantor of the financial report or solvability of the enterprise. The occurrence of deception efforts neatly planned by clients by hiding important information will not easily be exposed, nor will be the mistakes in the assessment of the auditor. However the possibilities of legal prosecution can be prevented if the public accountants carry out their professional services in accordance with the relevant technical and professional standards, and use their skills seriously and carefully in their jobs.Keywords: The public accountant profession, the auditor, Legal responsibility.